Pro-angiogenic gene expression is associated with better outcome on sunitinib in metastatic clear-cell renal cell carcinoma. (3rd April 2018) - Beuselinck, Benoit; Verbiest, Annelies; Couchy, Gabrielle; Job, Sylvie; de Reynies, Aurélien; Meiller, Clément; Albersen, Maarten; Verkarre, Virginie; Lerut, Evelyne; Méjean, Arnaud; Patard, Jean-Jacques; Laguerre, Brigitte; et al.
Abstract: Objectives: Clear-cell renal cell carcinomas (ccRCC) are characterized by hyper-vascularization and can respond to vascular endothelial growth factor receptor (VEGFR) inhibitors such as sunitinib. We aimed to study the predictive value of the expression of genes in the hypoxia induced factor (HIF) – vascular endothelial growth factor (VEGF) - VEGFR-pro-angiogenic pathway in metastatic ccRCC (m-ccRCC) patients treated with sunitinib and the correlation between the expression of these genes and the molecular ccrcc-classification, the expression of genes involved in the immune-suppressive microenvironment and Von Hippel-Lindau (VHL) - and Polybromo-1 (PBRM1) - mutational status. Material and methods: m-ccRCC patients treated with sunitinib as first-line targeted therapy were included. Gene expression was studied in the primary nephrectomy sample by qRT-PCR, VHL- and PBRM1-mutational status by sequencing. Response rate by RECIST, progression-free survival (PFS) and overall survival (OS) were study endpoints. Results: One hundred and four patients were included. On multivariate-analysis, HIF2A-, platelet derived growth factor receptor beta (PDGFRB)-, VEGFC-, VEGFR1- and VEGFR2-expression were correlated with PFS and HIF1A-, HIF2A-, VEGFR1- and VEGFR2-expression with OS. VEGFR2-expression showed the strongest association with outcome, being significantly correlated with all outcome parameters. HIF2A, VEGFA, VEGFR1, VEGFR2 and VEGFR3 were highly expressed in the transcriptomic ccrcc2-subtype of tumors, known to be highly sensitive to sunitinib. In the total tumor series, there was no correlation nor inverse correlation between the expression of genes involved in angiogenesis and in the immune-suppressive microenvironment. In tumors with a bi-allelic PBRM1-inactivation, HIF2A-, VEGFA-, VEGFR1- and VEGFR2-expression were higher, compared to tumors with one or two functional PBRM1-alleles. Conclusions: Intratumoral expression of genes involved in the HIF-VEGF-VEGFR-pro-angiogenic pathway, especially VEGFR2, is associated with favorable outcome on sunitinib in m-ccRCCs. Several genes involved in this pathway are upregulated in the molecular ccrcc2-subgroup, which usually responds well to sunitinib.